2022
DOI: 10.4111/icu.20220081
|View full text |Cite
|
Sign up to set email alerts
|

Different failure rates of insertion of 10/12-Fr ureteral access sheaths during retrograde intrarenal surgery in patients with and without stones

Abstract: Purpose The aim of this study was to compare the failure rates of insertion of a 10/12-Fr ureteral access sheath (UAS) during retrograde intrarenal surgery (RIRS) in cases with and without stones and to analyze the risk factors for UAS insertion failure. Materials and Methods A total of 640 RIRS cases (538 with and 102 without stones) were evaluated. The primary outcome of interest was the failure rate of insertion of a 10/12-Fr UAS. Associated risk factors were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For the RF group, RIRS was performed with first-look ureteroscopy using a semirigid ureteroscope under general anesthesia in all cases. 14 A hydrophilic guidewire was advanced to the ureter through the semirigid ureteroscope in the lithotomy position, following which the semirigid ureteroscope was advanced to the upper ureter or renal pelvis and the ureteral length was measured. After a hydrophilic guidewire was left in the renal pelvis as a safety wire, a superstiff guidewire (Amplatz Super Stiff, Boston Scientific, Malborough, Massachusetts) was placed and a UAS was inserted along the superstiff guidewire under direct vision of a semirigid ureteroscope introduced beside the UAS into the bladder to observe whether the UAS was properly inserted through the ureteral orifice without twisting in the bladder.…”
Section: Methodsmentioning
confidence: 99%
“…For the RF group, RIRS was performed with first-look ureteroscopy using a semirigid ureteroscope under general anesthesia in all cases. 14 A hydrophilic guidewire was advanced to the ureter through the semirigid ureteroscope in the lithotomy position, following which the semirigid ureteroscope was advanced to the upper ureter or renal pelvis and the ureteral length was measured. After a hydrophilic guidewire was left in the renal pelvis as a safety wire, a superstiff guidewire (Amplatz Super Stiff, Boston Scientific, Malborough, Massachusetts) was placed and a UAS was inserted along the superstiff guidewire under direct vision of a semirigid ureteroscope introduced beside the UAS into the bladder to observe whether the UAS was properly inserted through the ureteral orifice without twisting in the bladder.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Waseda et al reported that the different failure rates of insertion of 10/12-Fr access sheaths in patients with and without stones. 3 A total of 640 Japanese patients including 538 stone cases and 102 non-stones cases were examined. All of them were not pre-stented.…”
Section: Editorial Comment Editorial Comment To Evaluation Of Uretera...mentioning
confidence: 99%
“…RIRS requires repetitive scope insertion to fragment and extract urinary stones; thus, to aid access to the proximal ureter and renal pelvis and to lower intrarenal pressure, a ureteral access sheath (UAS) is widely used during RIRS. However, sometimes ureteral access is not possible-previous studies have reported 8.8% to 20% failure rates for UAS insertion [6]. For these failed cases, or when a tight ureter is expected, double-J ureteral stent insertion is recommended [7], because ureteral stenting induces passive dilation of the ureter, which facilitates passage of the UAS and ureterorenoscope [8].…”
Section: Introductionmentioning
confidence: 99%